Teletrabalho na administração pública federal: uma análise do potencial de implantação na diretoria de marcas do INPI - Freitas, Silvia Rodrigues de (2008)
This dissertation analyses the implementation of the telework project of the Marks Directorate at the Industrial Property National Institute, an agency of the Brazilian federal administration. The analysis focuses on the public servants and their expectations, since the work developed at the Marks Directorate is mainly based on the intellectual capital of its staff. This research first addresses the subject by describing the current technical and sociological context. In which information society and globalization's impact on labour's evolution, and information and communication technology's impact on e-government development are both considered as having important roles. A review of the state of the art on telework research is presented as the basis of the analyses, including a definition of telework and its most relevant aspects. National and international cases of telework, both in the public and private sector, are used as examples in the analyses. The matter of performance control and evaluation is also briefly addressed. In order to assess the viability of the implementation of telework, a review of the activities developed at the Marks Directorate is performed. Emphasis is given to the modernization of examining procedures, without disregarding administrative facts, such as the new career plan and its performance evaluation procedures, that might affect the telework project. The case study is conducted by means of a survey with open and closed questions served in a questionnaire. The analyses of the results leads to the conclusion that telework can be successfully implemented in the Marks Directorate, being also an opportunity to study the adaptation of a working practice originating at the private sector and applied in public administration, taking into account their differences.